2020
DOI: 10.1016/j.anaerobe.2020.102285
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia caused by Veillonella dispar in an oncological patient

Abstract: Veillonella dispar is a Gram-negative anaerobic coccus involved in only a few human diseases. We report the second case of bacteremia due to this microorganism in an elderly patient. A 72-year-old man with a history of bladder cancer presented with diarrhea, vomiting, and fever for 48 hours. After the diagnosis of septic shock, four sets of blood cultures were taken, and three of them yielded V. dispar. Resistance to metronidazole, penicillin, and piperacillin-tazobactam was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…rectale, R. intestinalis, R. hominis, V. atypical, R. gnavus, and L. salivarius, which were consistent with previous research (35). Our data then showed that 4 weeks of lactitol supplementation lead to decrease of cirrhosis-enriched species including pathogenic K. pneumonia (36) and V. dispar (37,38), and increase of some health-beneficial species including B. longum, B. pseudocatenulatum, L. salivarius and B. ovatus (39). Previous studies have also demonstrated that lactitol increased the abundance of the first two species in the gut (11).…”
Section: Discussionsupporting
confidence: 92%
“…rectale, R. intestinalis, R. hominis, V. atypical, R. gnavus, and L. salivarius, which were consistent with previous research (35). Our data then showed that 4 weeks of lactitol supplementation lead to decrease of cirrhosis-enriched species including pathogenic K. pneumonia (36) and V. dispar (37,38), and increase of some health-beneficial species including B. longum, B. pseudocatenulatum, L. salivarius and B. ovatus (39). Previous studies have also demonstrated that lactitol increased the abundance of the first two species in the gut (11).…”
Section: Discussionsupporting
confidence: 92%
“…In particular, 2 of the 3 top predictors ( Veillonella dispar and Veillonella infantium ) as well as 2 other species associated with ongoing symptomatic COVID-19 belong to the genus Veillonella . Members of this genus are gram-negative anaerobic coccus that can cause infection in humans ( 30 ). Specifically, V .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, two of the three top predictors (Veillonella dispar and Veillonella infantium) as well as 2 other species associated with ongoing symptomatic COVID-19 disease belong the genus Veillonella. Members of this genus are gram-negative anaerobic coccus that can cause infection in humans (30). Specifically, V. infantium has been found in the bronchoalveolar lavage fluid of the COVID-19 patients suggesting it is a significant co-infectious agent (31).…”
Section: Oral Microbiome Composition Predicts Ongoing Symptomatic Covid-19mentioning
confidence: 99%
“…Furthermore, Karl et al [49] showed that greater microbiota alpha diversity is not always related to gut health but may be associated with the growth of potentially harmful bacteria. This is supported by an increased abundance of the potentially pathogenic genus Veillonella [64,[66][67][68] in the gut of marathon runners [40,46,53]. Although Sheiman et al observed an increase in Veillonella relative abundance in marathon runners post-marathon and isolated a strain of Veillonella atypica from stool samples.…”
Section: Diversity Of the Human Gut Microbiotamentioning
confidence: 99%